2018
DOI: 10.1017/s1047951118000446
|View full text |Cite
|
Sign up to set email alerts
|

Administrative health databases for addressing emerging issues in adults with CHD: a systematic review

Abstract: The need for population-based studies of adults with CHD has motivated the growing use of secondary analyses of administrative health data in a variety of jurisdictions worldwide. We aimed at systematically reviewing all studies using administrative health data sources for adult CHD research from 2006 to 2016. Using PubMed and Embase (1 January, 2006 to 1 January, 2016), we identified 2217 abstracts, from which 59 studies were included in this review. These comprised 12 different data sources from six countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Although not designed for research purposes, administrative health databases have become powerful data sources for studying diseases or the long-term outcomes of procedures or health interventions [12], [13] because of their large sample sizes, comprehensive records, and very long observation periods, providing a further useful and feasible tool to quickly increase the body of knowledge of real-life data on one topic and to develop quality of care improvement programs.…”
Section: Introductionmentioning
confidence: 99%
“…Although not designed for research purposes, administrative health databases have become powerful data sources for studying diseases or the long-term outcomes of procedures or health interventions [12], [13] because of their large sample sizes, comprehensive records, and very long observation periods, providing a further useful and feasible tool to quickly increase the body of knowledge of real-life data on one topic and to develop quality of care improvement programs.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary data sources correspond to a rich source of information that have become extensively used over the recent years 345,346 . This SLR highlights the main characteristics of the 123 databases used for secondary research in Colombia identified in 323 articles.…”
Section: Discussionmentioning
confidence: 99%
“…Although networks typically involve primary data collection, registries or databases may collect primary medical or surgical data or may apply secondary analyses to existing data sources. 81,82 Other data collection platforms assemble referral centres to voluntarily share data to address specific research queries. Tools that merge patient management tasks, clinical data, and reporting functions have been launched and developed in Canada and elsewhere.…”
Section: The Data-to-evidence Gapmentioning
confidence: 99%
“…22,25 Since the publication of the first paper from the Qu ebec CHD database, there has been a steady increase in secondary analyses of similar data sources in Canada, 95 the US, and Europe. 82 International efforts are ongoing to identify innovative data sources. In the absence of unique identifiers made possible with universal health insurance, US data sources such as the National Inpatient Sample use episodes of care rather than patients as units of measurement.…”
Section: The Data-to-evidence Gapmentioning
confidence: 99%
See 1 more Smart Citation